Developing the multi-intelligences of our pupils and students - Merced Jr., Briccio M. (MultipleIntellgencesCCSALecture, 2014)
Multi-intelligence theory and strategies provide a framework and tools that can help teachers in designing classrooms, instruction, and curricula that meet the individual needs of many kinds of students. In today's increasing diversity among students in terms of language, culture, religions, ability, and experience successful schools use a variety of teaching approaches, engage with families and communities to support life-long learning, and keep students motivated to learn and create. It help teachers, students, and parents realize that there are multiple ways to learn and that they themselves possess multiple types of intellectual strengths and life skills, increase students? confidence and enthusiasm for learning, improve students? academic achievement, change teachers? perceptions of their students? learning abilities. Multi-intelligence unveils academic strengths and honors alternative ways of learning.